ANALISIS KEMAMPUAN LITERASI SAINS BERDASARKAN KERANGKA PISA DALAM MATA PELAJARAN IPA TERPADU - Afrida, Juniar (Universitas Jember, 2024)
The goal of education in the twenty-first century is to raise students' scientific literacy. According to the PISA study, Indonesian students have very low levels of scientific literacy, which can be attributed to curricular factors, teacher effectiveness, and student characteristics. Educating future physics teachers about literacy is important because it shapes their behaviour, thought processes, and sense of responsibility for the cosmos and society. Using a mixed methods, this study assesses the scientific literacy of UINAR students aspiring to become physics teachers. The findings indicate that a sufficient 56.27 is the average scientific literacy ability. The learning process is primarily conceptual in nature, with little emphasis on the development of critical thinking skills or enthusiasm for solving scientific literacy problems.